A Set of Fluorescent Protein-Based Markers for Major Vesicle Coat Proteins in Yeast - Xue-Fei Cui; Zheng-Tan Zhang; Jing Zhu; Li Cui; Zhiping Xie (Membranes)
In eukaryotic cells, vesicle-mediated transport interconnects the endomembrane system. These vesicles are formed by coat proteins via deformation of donor membranes. Here, we constructed a set of fluorescent protein-based markers for major coat protein complexes in the yeast model system, and examined their subcellular localization patterns. Our markers covered COPII, COPI, AP-1, AP-2, AP-3, and retromer complexes. Our live cell imaging demonstrates that COPII puncta were primarily associated with the endoplasmic reticulum (ER), and occasionally with early Golgi. COPI was present on both early Golgi and late Golgi/early endosomes. AP-1 puncta were present on late Golgi/early endosomes. AP-2 was present on plasma membrane (PM)-associated puncta, and around the bud neck. AP-3 puncta were present on late Golgi/early endosomes and on the surface of vacuoles. Retromer was present on the surface of vacuoles, late endosomes, and other perivacuolar puncta. Notably, more than half of AP-1 puncta and AP-3 puncta were not associated with the donor compartments where they are thought to be generated, implying that these were coated transport vesicles. This work provides a convenient tool set for the investigation of vesicular transport in yeast and live cell imaging evidence for the presence of certain coated transport vesicles.